Content Analysis of STEM Integration in School Books: Comparison Between Indonesia and the Philippines - Pramesti G. S Kesturi; Nurma Yunita Indriyanti; Leonilla Baltazar; Louie Dasas (Jurnal Pendidikan Sains Indonesia, 2025)
Indonesia and the Philippines ranked low in scientific literacy based on the results of PISA 2022, reflecting that the integration of science, technology, engineering, and mathematics (STEM) in the curriculum of both countries is still not optimal. The level of STEM integration in textbooks represents how STEM is embedded in the curriculum at the national level. This study aims to investigate the integration of STEM ntegration in grade 8 junior high school science textbooks from Indonesia and the Philippines. Using a qualitative content analysis approach, six textbooks, three from each country, were analyzed using a rubric adapted from 24 indicators across six STEM integration pair combinations and three integration levels that are multidisciplinary, interdisciplinary, and transdisciplinary. The results show that both countries textbooks dominant at multidisciplinary level integration, with science-technology (S-T) being the most frequently integrated pairs. Indonesian textbooks demonstrate a wider range of integration levels, including transdisciplinary tasks linked to real-world contexts, while Philippine textbooks offer broader pairs coverage, including technology-mathematics (T-M) and engineering-mathematics (E-M) that cannot be dound in Indonesian textbooks, but lack transdisciplinary examples. The findings highlight similarities in dominant integration pairs and integration levels, as well as key differences in depth and contextual relevance of STEM integration. The findings also indicate both Indonesia and Philippines already following the trend of STEM integration in developed countries that dominant at S-T integration, but both Indonesia and Philippines need to optimize the level of integration to at least interdisciplinary level. These insights can inform future textbook development and STEM curriculum implementation